2012
DOI: 10.1002/mar.20533
|View full text |Cite
|
Sign up to set email alerts
|

Trust, Commitment, and Older Women: Exploring Brand Attachment Differences in the Elderly Segment

Abstract: Understanding older adults’ product consumption behavior is of high importance to consumer and marketing research. Prior studies have mainly focused on older adults’ cognitive decline and compared their behavior to that of younger consumers. A neglected area of research has been older consumers’ brand attachment that is associated with potential differences between consumers in their fifties and in their seventies. In this article, the authors provide insights into the under‐researched field of elderly women's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 71 publications
1
83
0
1
Order By: Relevance
“…While two powerful antecedents of brand commitment recognised in the review are satisfaction (Sung and Choi, 2010) and trust (Lacey, 2007), it is emphasised on the construct's capacity to accurately predict repurchase intentions (Jones et al, 2010) and positive word-of-mouth (Albert and Merunka, 2013). Among the most relevant antecedents of brand commitment are trust (Jahn et al, 2012;Lacey, 2007) and attachment to the brand (Ilicic and Webster, 2014). Commitment acts as the mediator between brand satisfaction and repurchase and advocacy intentions (Fullerton, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While two powerful antecedents of brand commitment recognised in the review are satisfaction (Sung and Choi, 2010) and trust (Lacey, 2007), it is emphasised on the construct's capacity to accurately predict repurchase intentions (Jones et al, 2010) and positive word-of-mouth (Albert and Merunka, 2013). Among the most relevant antecedents of brand commitment are trust (Jahn et al, 2012;Lacey, 2007) and attachment to the brand (Ilicic and Webster, 2014). Commitment acts as the mediator between brand satisfaction and repurchase and advocacy intentions (Fullerton, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Amine (1998) Trust is one of the most cited antecedents of brand commitment (e.g. Jahn et al, 2012;Lacey, 2007;Louis and Lombart, 2010). Trust is viewed as consumer's expectations that the brand can be relied on to deliver what it promises (Lacey, 2007).…”
Section: Brand Commitment As An Outcomementioning
confidence: 99%
“…Brand attachment is a relationship-based concept that addresses the bond between a consumer and a brand [24,25]. Prior research indicates that the brand attachment process can be characterized with four factors [10]: self-congruence, partner quality, trust, and commitment. Self-congruence and partner quality represent the degree to which a consumer is attached to a brand, while trust and commitment are the outcomes of that attachment.…”
Section: Brand Attachment Processmentioning
confidence: 99%
“…We develop a research model by proposing that consumer participation may be a positive consequence of their brand attachment process on these microblogs. As Jahn et al [10] indicated, the brand attachment process addresses the relationships among four factors: self-congruence, partner quality, trust, and commitment. The idea is that a consumer is likely to develop trust and commitment toward a brand, if s/he perceives high self-congruence and partner quality with it.…”
mentioning
confidence: 98%
“…Their studies concluded that older consumers exhibited a propensity to remain attached for a longer duration to the same preferred brand of perfume. In another study on older consumers by Jahn, Gaus and Kiessling (2012), they found that the older elderly (i.e. aged above 65 years) were more emotionally attached to their coffee brands than the younger elderly consumers (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%